Endoparasitic Gall Mites: Two New Novophytoptus Species (Eriophyoidea, Phytoptidae) from Southern African Sedges (Cyperaceae, Carex) and New Hypotheses on the Phylogeny of Novophytoptines - Philipp E. Chetverikov; Charnie Craemer; Vladimir D. Gankevich; Maria V. Kremenetskaya; Igor V. Kuzmin; Anna S. Zhuk (Diversity, 2023)
Eriophyoid mites (Acariformes, Eriophyoidea) are microscopic chelicerates morphologically greatly preadapted to endoparasitism on plants. Members of at least six phylogenetically distant eriophyoid genera from two families homoplastically transitioned to endoparasitism and acquired the ability to penetrate under the plant epidermis and feed on parenchymatous cells, usually causing necrosis. Theoretically, endoparasites are expected to show patterns of codivergence with hosts more than ectoparasites. Novophytoptus Roivainen 1947 is the only eriophyoid genus comprising exclusively endoparasitic species living in subepidermal tissues of herbaceous monocots of three families of the order Poales: Cyperaceae, Juncaceae, and Poaceae. Here, we described two new endoparasitic species, N. limpopoensis n. sp. and N. zuluensis n. sp., from southern African sedges Carex spicatopaniculata Boeckeler ex C.B.Clarke and C. zuluensis C.B.Clarke, respectively, and investigated the Cox1 phylogeny of Novophytoptus. Contrary to expectations, molecular phylogenetics did not recover host-specific mite clades associated with Cyperaceae and Juncaceae, but revealed geographical groups of Novophytoptus species from Africa and Eurasia. Our results provide a substantial basis for future coevolutionary studies on novophytoptines, which will be possible when more species and sequences of Novophytoptus from geographically remote regions and from diverse hosts representing all major clades of Poales become available for analyses.